Talazoparib in Patients with a Germline BRCA‐Mutated Advanced Breast Cancer: Detailed Safety Analyses from the Phase III EMBRACA Trial - Hurvitz, Sara A. (Oncologist, 2019)
BACKGROUND: In the EMBRACA phase III study (NCT01945775), talazoparib was associated with a significantly prolonged progression‐free survival (PFS) compared with physician's choice of chemotherapy (PCT) in germline BRCA1/2‐mutated HER2‐negative advanced breast cancer (ABC). Herein, the safety profile of talazoparib is explored in detail. MATERIALS AND METHODS: Overall, 412 patients received ≥1 dose of talazoparib (n = 286) or PCT (n = 126). Adverse events (AEs) were evaluated, including timing, duration, and potential overlap of selected AEs. The relationship between talazoparib plasma exposure and grade ≥3 anemia was analyzed. Time‐varying Cox proportional hazard models assessed the impact of dose reductions on PFS. Patient‐reported outcomes (PROs) in patients with common AEs and health resource utilization (HRU) were assessed in both treatment arms. RESULTS: The most common AEs with talazoparib were hematologic (195 [68.2%] patients) and typically occurred within the first 3–4 months of receiving talazoparib. Grade 3‐4 anemia lasted approximately 7 days for both arms. Overlapping grade 3‐4 hematologic AEs were infrequent with talazoparib. Higher talazoparib exposure was associated with grade ≥3 anemia. Permanent discontinuation of talazoparib due to hematologic AEs was low (<2%). A total of 150 (52.4%) patients receiving talazoparib had AEs associated with dose reduction. Hematologic toxicities were managed by supportive care medication (including transfusion) and dose modifications. Among patients with anemia or nausea and/or vomiting AEs, PROs favored talazoparib. After accounting for the treatment‐emergent period, talazoparib was generally associated with a lower rate of hospitalization and supportive care medication use compared with chemotherapy. CONCLUSION: Talazoparib was associated with superior efficacy, favorable PROs, and lower HRU rate versus chemotherapy in gBRCA‐mutated ABC. Toxicities were manageable with talazoparib dose modification and supportive care. IMPLICATIONS FOR PRACTICE: Talazoparib was generally well tolerated in patients with germline BRCA‐mutated HER2‐negative advanced breast cancer in the EMBRACA trial. Common toxicities with talazoparib were primarily hematologic and infrequently resulted in permanent drug discontinuation (<2% of patients discontinued talazoparib due to hematologic toxicity). Hematologic toxicities typically occurred during the first 3–4 months of treatment and were managed by dose modifications and supportive care measures. A significant efficacy benefit, improved patient‐reported outcomes, lower rate of health resource utilization and a tolerable safety profile support incorporating talazoparib into routine management of germline BRCA‐mutated locally advanced/metastatic breast cancer.